Polyimide aerogel fiber and preparation method and application thereof
Patent Information
- Application Number
- CN202610870528.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-16
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]本申请旨在提供一种聚酰亚胺气凝胶纤维及其制备方法与应用,以解决现有技术中气凝胶纤维机械性能差、制备工艺复杂、难以连续生产及缺乏智能感知功能的技术问题
本申请制备的聚酰亚胺气凝胶纤维具有独特的皮芯结构,皮层致密,提供机械强度,芯层多孔,保障隔热性能,制备的聚酰亚胺气凝胶纤维断裂强度≥20MPa(最高可达24.8MPa),孔隙率80%-98%,密度低至0.008-0.010g/cm³,热导率35-190mW/(m·K),使用温度范围宽达-170℃-400℃。
Smart Images

Figure CN122959862A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of functional fiber materials technology, specifically relating to a polyimide aerogel fiber, its preparation method, and its application. Background Technology
[0002] Traditional firefighting suits typically consist of multiple layers of flame-retardant materials, heat insulation layers, and waterproof and breathable layers, making them relatively heavy (approximately 3-5 kg). Prolonged wear can easily lead to neck and shoulder fatigue, sluggish movement, and impaired mobility on the fire scene. Furthermore, the limited breathability of traditional firefighting suits can create a hot and humid microclimate inside, causing heat stress. In addition, traditional firefighting suits lack real-time temperature sensing and high-temperature warning functions, making it difficult to detect heat damage before visible damage to the fabric occurs, posing a significant safety hazard.
[0003] Aerogels have attracted much attention in the field of thermal insulation due to their high porosity, low density, and low thermal conductivity. However, traditional aerogels have poor mechanical properties, complex preparation processes, and high costs. In particular, polyimide aerogel fibers have problems such as low molding efficiency, difficulty in continuous production, excessively large pore size, and the need for complex post-processing (such as supercritical drying) in traditional preparation methods, which limit their application in actual fire suits.
[0004] Therefore, it is necessary to develop a polyimide aerogel fiber that is lightweight, has high mechanical strength, high porosity, can be continuously produced, and has intelligent sensing capabilities. Summary of the Invention
[0005] This application aims to provide a polyimide aerogel fiber, its preparation method and application, to solve the technical problems of poor mechanical properties, complex preparation process, difficulty in continuous production and lack of intelligent sensing function of aerogel fibers in the prior art.
[0006] To achieve the above objectives, this application provides the following technical solution: In a first aspect, this application provides a method for preparing polyimide aerogel fibers, comprising the following steps: S1: Imidization of fluorinated polyimide Under an inert gas atmosphere, 4,4'-diaminodiphenyl ether (ODA) and 3,5-diaminobenzoic acid (DABA) are dissolved in N-methylpyrrolidone (NMP), and then hexafluorodianhydride (6FDA) and pyromellitic dianhydride (PMDA) are added to react and generate a polyamic acid (PAA) solution. Isoquinoline and copper chloride (CuCl2) are added to a polyamic acid (PAA) solution to form an organically soluble polyamic acid solution; A solution of imidized fluorinated polyimide was prepared by adding perfluoroethylene propylene copolymer (FEP) and molybdenum disulfide (MoS2) to an organic soluble polyamic acid solution and heating it for imidization. S2: Functionalization of imidized fluorinated polyimide A photosensitive crosslinking agent was prepared by dissolving hydroxyethyl methacrylate (HEMA), dicyclohexylcarbodiimide (DCC), and 4-dimethylaminopyridine (DMAP) in N-methylpyrrolidone. An imidized fluorinated polyimide solution and Irgacure 2100 photoinitiator were added to a photosensitive crosslinking agent to carry out an esterification reaction, thereby obtaining a crosslinked polyimide solution. S3: Preparation of polyimide aerogel fibers The prepared cross-linked polyimide solution was subjected to conjugated electrospinning, and the spun fibers were simultaneously subjected to ultraviolet irradiation to carry out sol-gel transformation, thereby obtaining spun filaments. Polyimide aerogel fibers with a core-sheath structure are obtained by exchanging the solvent in a condensation bath with spun filaments.
[0007] Furthermore, in step S1, the inert gas protective atmosphere is a nitrogen protective atmosphere.
[0008] The purpose of introducing nitrogen is to create a dry, oxygen-free, inert environment inside the reaction vessel to prevent the polyamic acid intermediate from being oxidized or hydrolyzed and degraded, thereby ensuring the synthesis of high molecular weight, high-quality polyimide precursors.
[0009] Further, in step S1, the molar ratio of 4,4'-diaminodiphenyl ether to 3,5-diaminobenzoic acid is 1:(1-1.3); preferably, the molar ratio of 4,4'-diaminodiphenyl ether to 3,5-diaminobenzoic acid is 1:1.2.
[0010] In the preparation of polyimide aerogel fibers, 4,4'-diaminodiphenyl ether, as the main diamine monomer, provides the flexibility and mechanical strength of the molecular chain, ensuring that the fiber has good spinnability and structural stability. 3,5-diaminobenzoic acid, as a functionalized diamine comonomer, provides key reaction sites for subsequent grafting of photosensitive crosslinking agents through its carboxyl groups (-COOH). The copolymerization of these two components ensures the mechanical properties and flexibility of the polyimide matrix, while 3,5-diaminobenzoic acid introduces carboxyl side groups that can be modified, together constructing a polyimide molecular skeleton that meets both fiber forming and processing requirements and enables rapid UV crosslinking.
[0011] Furthermore, in step S1, the molar ratio of hexafluorodianhydride to pyromellitic dianhydride is 1:(1-1.5), preferably, the molar ratio of hexafluorodianhydride to pyromellitic dianhydride is 1:1.
[0012] In this application, hexafluorodianhydride and pyromellitic dianhydride constitute a dianhydride copolymer system that combines rigidity and flexibility. Hexafluorodianhydride provides fluorinated structural units, and its core function is to improve the solubility of polyimide, creating conditions for subsequent solution spinning and functionalization reactions. Pyromellitic dianhydride provides rigid benzene ring structural units, and its core function is to impart high mechanical strength and high thermal stability to the fibers. The combined use of hexafluorodianhydride and pyromellitic dianhydride enables the prepared polyimide aerogel fibers to simultaneously possess good solubility, ease of processing, high mechanical strength, and wide-temperature-range thermal stability.
[0013] Furthermore, the reaction conditions for generating the polyamic acid solution in step S1 are continuous stirring for 10-14 hours.
[0014] Furthermore, in step S1, isoquinoline and copper chloride are added to the polyamic acid solution, such that the mass concentrations of isoquinoline and copper chloride in the reaction solution are 5-20 wt% and 2.5-10 wt%, respectively.
[0015] Furthermore, in step S1, isoquinoline and copper chloride are added to the polyamic acid solution, and the mixture is stirred continuously for 3-5 hours.
[0016] Isoquinoline is a nitrogen-containing heterocyclic organic base that acts as a catalyst / dehydrating agent in the synthesis of polyimide to promote imidization reactions. Isoquinoline can promote the cyclization and dehydration reaction of polyamic acid, accelerating its conversion into polyimide. During imidization, isoquinoline acts as a proton absorber, neutralizing acids (such as water or small molecule acids) generated in the reaction and shifting the reaction equilibrium towards the formation of polyimide. Adding an isoquinoline basic catalyst allows imidization to be completed at a lower temperature, reducing energy consumption and avoiding high-temperature degradation of the polymer chains.
[0017] Copper chloride acts as a catalyst in the synthesis of polyimide, accelerating the imidization reaction, promoting the condensation reaction between the carboxyl and amide groups of polyamic acid, and speeding up the cyclization and dehydration process. As a metal salt catalyst, copper chloride works synergistically with isoquinoline, and the combined effect of both significantly improves the rate and conversion of the imidization reaction. Furthermore, copper chloride can influence the conformation and arrangement of polyimide molecular chains, helping to reduce strong interactions between molecular chains (such as π-π stacking), increasing the free volume of the molecular chains, thereby improving the solubility of polyimide in organic solvents and facilitating subsequent spinning processes.
[0018] The synergistic catalytic effect of isoquinoline and copper chloride enables the generated polyimide precursor to have better organic solvent solubility, creating conditions for subsequent photosensitive grafting and electrospinning.
[0019] Furthermore, in step S1, the amount of perfluoroethylene propylene copolymer added is 5-20 wt%, the amount of molybdenum disulfide added is 2.5-10 wt%, and the theoretical yield of polyimide is calculated based on the total amount of hexafluorodianhydride and pyromellitic dianhydride monomers.
[0020] Both perfluoroethylene propylene copolymer and molybdenum disulfide are used as functional additives. Perfluoroethylene propylene copolymer is used to toughen and improve hydrophobicity, while molybdenum disulfide is used to improve triboelectric properties and some thermal insulation properties.
[0021] Perfluoroethylene propylene copolymer is physically blended into a polyimide matrix. Specifically, the perfluoroethylene propylene copolymer is added during the solution stage of polyamic acid. After thorough stirring and dispersion, the perfluoroethylene propylene copolymer is softened by segmented heating imidization and physically entangled with the forming three-dimensional polyimide network. Due to the low surface energy of the perfluoroethylene propylene copolymer, it tends to migrate to the fiber surface during fiber forming, forming a surface enrichment layer, thereby giving the fiber excellent hydrophobic and oil-repellent properties. The perfluoroethylene propylene copolymer is dispersed in the fiber in the form of nanoparticles, which plays a role in toughening and improving processing fluidity.
[0022] Molybdenum disulfide, as a functional nanofiller, improves the mechanical strength and wear resistance of fibers by forming a nanocomposite structure with the polyimide matrix. On the other hand, it enables fiber fabrics to have stable electrical signal output capabilities over a wide temperature range by utilizing its excellent piezoelectric and triboelectric properties.
[0023] The synergistic effect of perfluoroethylene propylene copolymer and molybdenum disulfide enables the subsequently prepared polyimide aerogel fiber fabric to possess lightweight, high flexibility, wide temperature range thermal insulation, and intelligent sensing functions.
[0024] Furthermore, the heating imidization treatment in step S1 adopts a staged heating process, specifically: treatment at 100℃, 200℃ and 250℃ for 0.8-1.5h respectively.
[0025] Step S1 employs a stepped heating imidization process, with treatments at 100℃, 200℃, and 250℃ for 0.8-1.5 hours each. The aim is to gradually and completely drive the thermal cyclization and dehydration reaction of polyamic acid to convert it into polyimide by progressively increasing the reaction temperature. Specifically, the 100℃ treatment stage slowly removes physically adsorbed solvent and some water of crystallization, preventing rapid imidization that could lead to molecular chain breakage or incomplete cyclization. The 200℃ treatment stage promotes moderate cyclization and dehydration of the polyamic acid, forming a partially imidized structure. The 250℃ treatment stage ensures complete imidization, yielding high molecular weight polyimide with a high degree of imidization. This staged heating method can effectively avoid the thermal degradation of molecular chains, uneven cross-linking, or collapse of pore structure caused by rapid high-temperature reactions, thereby ensuring that the final polyimide matrix has a complete molecular chain structure, excellent mechanical properties, and stable chemical properties, providing a high-quality matrix material for subsequent functionalization grafting and electrospinning.
[0026] Furthermore, in step S2, the total amount of hydroxyethyl methacrylate, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine is 10wt%. Based on the theoretical yield of polyimide calculated from the total amount of hexafluorodianhydride and pyromellitic dianhydride monomers fed in step S1, the mass ratio of hydroxyethyl methacrylate, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine is 1:(1-2):(1-2).
[0027] Furthermore, in step S2, the mass ratio of the imidized fluorinated polyimide solution to the Irgacure 2100 photoinitiator is (20-100):1.
[0028] Furthermore, the process conditions for the esterification reaction in step S2 are: temperature 20-30℃, continuous stirring reaction for 20-28h.
[0029] Furthermore, the grafting rate of hydroxyethyl methacrylate in the crosslinked polyimide solution obtained in step S2 is 25-100%.
[0030] The grafting rate is the percentage of hydroxyethyl methacrylate successfully grafted onto the polyimide molecular chain out of the total mass of hydroxyethyl methacrylate input.
[0031] In step S2, hydroxyethyl methacrylate, as a photosensitive crosslinking monomer, undergoes an esterification reaction between its hydroxyl groups (-OH) and the carboxyl groups (-COOH) of the polyimide side chain, grafting photocrosslinkable carbon-carbon double bonds (C=C) onto the polyimide molecular chain, endowing the polyimide with UV responsiveness and providing crosslinking sites for the subsequent rapid sol-gel transition. Dicyclohexylcarbodiimide, as a dehydration condensation catalyst, activates the carboxyl groups of the polyimide side chain, promoting its esterification reaction with the hydroxyl groups of hydroxyethyl methacrylate, thereby improving grafting efficiency and reaction rate. 4-Dimethylaminopyridine, as a highly efficient catalyst for the acylation reaction, synergistically accelerates the esterification reaction with dicyclohexylcarbodiimide while suppressing side reactions, improving the yield and selectivity of the grafting reaction. Irgacure The 2100 photoinitiator decomposes under UV irradiation to generate free radicals, initiating rapid cross-linking polymerization of the carbon-carbon double bonds on the hydroxyethyl methacrylate grafted chains. This allows the cross-linked polyimide solution to complete the sol-gel transition within 10 minutes, forming a high-strength gel network. Dicyclohexylcarbodiimide and 4-dimethylaminopyridine synergistically catalyze the grafting of hydroxyethyl methacrylate onto the polyimide chains. Irgacure 2100 endows the system with rapid UV cross-linking capability. Together, these four components achieve the photosensitive functionalization and rapid gelation of the polyimide.
[0032] Furthermore, the process of conjugate electrospinning in step S3 is as follows: spinning voltage 20-30kV, receiving distance 17-21cm, and liquid supply rate 0.4-1.2mL / h.
[0033] Furthermore, the ultraviolet radiation intensity of the ultraviolet irradiation in step S3 is 500-1000 W / m².
[0034] The purpose of controlling the ultraviolet radiation intensity within the range of 500-1000 W / m² is to achieve a match between the photoinitiated crosslinking rate and the spinning process. If the intensity is too low, the concentration of free radicals generated by the decomposition of the photoinitiator will be insufficient, resulting in an excessively long sol-gel transition time. This will prevent the fiber from forming a sufficiently strong gel network before entering the condensation bath, easily leading to fiber deformation, filament bundling, or collapse of the pore structure. If the intensity is too high, the crosslinking reaction will be too vigorous, causing an excessively dense crosslinked layer to form instantly on the fiber surface. This will not only hinder further reactions of the residual double bonds in the core, leading to uneven crosslinking, but may also cause surface cracks or increased brittleness due to excessive shrinkage stress. Therefore, the selection of ultraviolet irradiation intensity must ensure that moderate and uniform gelation is completed along the fiber's flight path during electrospinning, guaranteeing fiber morphology fixation and structural stability during subsequent atmospheric pressure drying, and avoiding brittle defects caused by excessive crosslinking.
[0035] Furthermore, the sol-gel transition time in step S3 is 10-15 min.
[0036] Furthermore, the ambient temperature for preparing the spinning filaments in step S3 is 25-30℃, and the humidity is 36-50%.
[0037] Step S3 specifies clear requirements for ambient temperature (25-30℃) and humidity (36-50%). The purpose is to precisely control the solvent evaporation rate, phase separation kinetics, and electrostatic dissipation ability during electrospinning. A suitable temperature (25-30℃) allows the N-methylpyrrolidone solvent to evaporate at an appropriate rate, avoiding insufficient fiber solidification and adhesion due to excessively low temperature, or nozzle clogging and uneven fiber diameter due to excessively high temperature. A suitable humidity (36-50%) induces phase separation through gentle water vapor, promoting the formation of a uniform nanoporous structure inside the fiber. At the same time, it avoids insufficient pore development due to excessively low humidity, or excessively thick skin or even surface collapse due to excessively high humidity. It can also effectively dissipate electrostatic accumulation to ensure jet stability, thereby ensuring a continuous and stable spinning process and obtaining polyimide aerogel fibers with uniform diameter, complete pore structure, and good core-skin morphology.
[0038] Furthermore, the process for the condensation bath in step S3 is as follows: The spun filaments are sequentially passed through the first bath of 20-60 wt% HCOOH or CH3COOH aqueous solution for 0.8-1.5 h, the second bath of deionized water for 3-5 h, and the third bath of ethanol for 0.5-1 h.
[0039] Furthermore, the temperature of the first bath, consisting of a 20-60 wt% HCOOH or CH3COOH aqueous solution, is 42-47℃, and the time for the spinning filaments to pass through the first bath is 0.8-1.5 h. The temperature of the deionized water in the second bath is 60-90℃, and the spinning filaments pass through the second bath for 3-5 hours. The temperature of the ethanol in the third bath is 25-35℃, and the time for the spinning filaments to pass through the third bath is 0.5-1h. Preferably, the temperature of the first bath of 20-60 wt% HCOOH or CH3COOH aqueous solution is 45°C, and the time for the spinning filaments to pass through the first bath is 1 hour; The temperature of the deionized water in the second bath is 75℃, and the spinning filaments pass through the second bath for 4 hours. The ethanol temperature in the third bath is 30℃, and the spinning filaments pass through the third bath for 0.5 hours.
[0040] Step S3 employs a series of condensation bath processes: acid bath (HCOOH or CH3COOH aqueous solution) - deionized water - ethanol, with the temperature controlled between 30-90℃. The purpose is to induce the formation and solidification of the core-skin structure through gradient solvent exchange; the HCOOH in the first bath (acid bath)... +It can neutralize the carboxylate anions on the polyamic acid or photosensitive polyimide (hydroxyethyl methacrylate grafted) chains, reduce the electrostatic repulsion between molecular chains, promote the aggregation and contraction of molecular chains and preferentially migrate to the fiber surface to form a dense skin layer; then entering the second bath (deionized water) and the third bath (ethanol) can gradually replace the residual acid and organic solvent inside the fiber, reduce the surface tension, and effectively prevent the pore structure from collapsing due to capillary force when drying at room temperature and pressure. At the same time, the temperature is controlled at 30-90℃ to accelerate the solvent exchange rate, avoiding incomplete exchange and insufficient skin layer formation due to too low temperature, or excessive fiber shrinkage and decreased porosity due to too high temperature, thus ensuring that the final fiber has a gradient network structure with a dense skin layer and a porous core layer.
[0041] Furthermore, in step S3, after the spinning filaments undergo solvent exchange in a condensation bath, they are dried at room temperature and pressure to obtain polyimide aerogel fibers with a core-sheath structure.
[0042] Secondly, this application provides a polyimide aerogel fiber, which is prepared by the preparation method described in the first aspect.
[0043] Furthermore, the polyimide aerogel fiber contains a fluorinated polyimide matrix, 25-100% grafted hydroxyethyl methacrylate, 2.5-10 wt% doped molybdenum disulfide, and 5-20 wt% perfluoroethylene propylene copolymer.
[0044] Furthermore, the polyimide aerogel fiber has a core-sheath structure, wherein the sheath layer in the core-sheath structure has a dense structure and is formed by the migration of polyamic acid to the fiber surface under the action of hydrogen ions; and the core layer in the core-sheath structure has a porous network structure.
[0045] Furthermore, the polyimide aerogel fiber has a porosity of 80%-98%, a density of 0.008-0.010 g / cm³, a tensile strength ≥20 MPa, a thermal conductivity of 35-190 mW / (m·K), and an operating temperature range of -170℃ to 400℃.
[0046] Thirdly, this application provides a fabric comprising polyimide aerogel fibers prepared by the preparation method described in the first aspect.
[0047] Furthermore, the fabric includes a fabric layer and a conductor; the fabric layer is woven from the polyimide aerogel fibers by a weaving machine; the conductor connects all the polyimide aerogel fibers in the fabric layer; the fabric constitutes a single electrode.
[0048] Fourthly, this application provides a method for preparing the fabric described in the third aspect, comprising the following steps: Polyimide aerogel fibers are woven into a fabric layer using a braiding machine, and all the polyimide aerogel fibers in the fabric layer are connected by wires to obtain a fabric that constitutes a single electrode.
[0049] Fifthly, this application provides an intelligent firefighting suit, including the fabric described in the third aspect and a signal processing and early warning module; the signal processing and early warning module includes a microprocessor, a wireless communication unit and an alarm unit, used to collect the electrical signals generated by the single electrode, identify the firefighter's movement status and abnormal ambient temperature, and issue an early warning.
[0050] This application utilizes an integrated process of electrospinning, ultraviolet irradiation, condensation bath collection, and solvent exchange to achieve adequate external reinforcement, dynamic gelation, and rapid sol-gel transition, thereby rapidly and scalably preparing polyimide aerogel fibers with a core-sheath structure. The specific structure is as follows: Functional group grafting region: Photosensitive polyimide was synthesized by grafting hydroxyethyl methacrylate onto an organically soluble polyimide chain via a Steglich esterification reaction between the carboxyl group on polyimide and the hydroxyl group on hydroxyethyl methacrylate. The introduction of the -CF3 group in the polyimide backbone effectively increases the free volume between molecular chains, reduces the regularity of molecular chain segments, and reduces the π-π interactions between benzene rings, thereby producing a polyimide with good solubility.
[0051] UV-enhanced cross-linking region: By introducing the Irgacure 2100 photoinitiator, the hydroxyethyl methacrylate-functionalized crosslinked polyimide solution can be rapidly transformed into a sol-gel conversion under ultraviolet light irradiation. In the UV-enhanced dynamic gelation strategy at 500-1000 W / m², the randomly distributed polyimide chains are rapidly crosslinked by UV irradiation, resulting in a highly crosslinked and high-strength gel network.
[0052] Continuous polyimide aerogel fiber forming area: Cross-linked polyimide solution is used as the spinning solution to form filaments under electrospinning. In the subsequent acidic condensation bath, the freely entangled cross-linked polyimide molecular chains are ionized by hydrogen ions (H+). + Under the influence of the solvent exchange in the condensation bath, the cross-linked polyimide in the fiber core cannot completely migrate to the surface due to the slow diffusion rate, forming a loose core layer. This results in a polyimide aerogel fiber with a high-strength surface layer and a loose gradient network structure. Finally, it is woven into a large-size polyimide aerogel fiber fabric using a semi-automatic loom. This preparation method is expected to be a promising alternative for high-throughput and large-scale manufacturing of aerogel fibers / fabrics.
[0053] Compared with the prior art, this application includes the following beneficial technical effects: The polyimide aerogel fiber prepared in this application has a unique core-sheath structure. The dense sheath provides mechanical strength, while the porous core ensures thermal insulation performance. The prepared polyimide aerogel fiber has a tensile strength ≥20MPa (up to 24.8MPa), a porosity of 80%-98%, a density as low as 0.008-0.010g / cm³, a thermal conductivity of 35-190mW / (m·K), and a wide operating temperature range of -170℃ to 400℃.
[0054] This application grafts the photosensitive crosslinking agent hydroxyethyl methacrylate onto the polyimide molecular chain and introduces Irgacure 2100 photoinitiator, simultaneously performing ultraviolet irradiation (500-1000W / m²) during electrospinning, thereby shortening the sol-gel transition time from more than 12 hours in the traditional process to less than 10 minutes, making it suitable for large-scale continuous production.
[0055] This application utilizes a series of condensation baths (acid-water-ethanol) to achieve gradient solvent exchange, where H+ in the acidic condensation bath... + The polyamic acid molecular chains are induced to migrate to the fiber surface, forming a dense skin layer. During subsequent solvent exchange, the polyamic acid in the core cannot completely migrate, retaining the porous structure. This skin-core structure enables the fiber to achieve both high strength and high porosity, overcoming the limitation of traditional aerogel fibers where strength and thermal insulation cannot be simultaneously achieved.
[0056] This application endows polyimide aerogel fibers with excellent triboelectric output properties by doping them with molybdenum disulfide nanoflowers. The polyimide aerogel fiber fabric maintains a stable electrical signal output over a wide temperature range. By integrating this fabric with a signal processing module, it is possible to monitor firefighters' different movement states in real time, such as walking slowly, walking normally, walking briskly, running, and jumping, and issue early warnings when temperatures are abnormal, significantly improving the safety of fire rescue.
[0057] The perfluoroethylene-propylene copolymer added in this application has extremely low surface energy, which spontaneously migrates to the surface during fiber forming to form a hydrophobic enrichment layer, giving the fire suit water-repellent, oil-repellent, and self-cleaning properties. Simultaneously, the perfluoroethylene-propylene copolymer, as a soft segment polymer, acts as an internal plasticizer, improving the fiber's flexibility and facilitating subsequent weaving processes.
[0058] In summary, this application utilizes innovative processes such as fluorinated copolymerization of hexafluorodianhydride and pyromellitic dianhydride with 3,5-diaminobenzoic acid carboxyl functionalization, photosensitive grafting of hydroxyethyl methacrylate with UV synchrotron radiation electrospinning, and gradient condensation bath-induced core-sheath structure formation to prepare polyimide aerogel fibers possessing high tensile strength (≥20 MPa), high porosity (80%-98%), ultra-low density (0.008-0.010 g / cm³), and wide-temperature-range thermal stability (-170-400℃). Compared with traditional technologies, this application shortens the sol-gel transition time from over 12 hours to less than 10 minutes, obtains a complete porous structure without supercritical drying, and imparts stable triboelectric output across a wide temperature range through molybdenum disulfide doping, while blending with perfluoroethylene-propylene copolymer imparts hydrophobic self-cleaning properties. This achieves lightweight thermal insulation and intelligent motion sensing, providing an efficient and low-cost method for the large-scale production of intelligent fire-fighting suits. Attached Figure Description
[0059] The present application will be described in further detail below with reference to the accompanying drawings and preferred embodiments. However, those skilled in the art will understand that these drawings are drawn only for the purpose of explaining the preferred embodiments and therefore should not be construed as limiting the scope of this disclosure. Furthermore, unless specifically indicated, the drawings are only schematic representations of the composition or structure of the described objects and may contain exaggerated depictions, and the drawings are not necessarily drawn to scale.
[0060] Figure 1 The reaction principle of the preparation method of polyimide aerogel fiber.
[0061] Figure 2 This is a schematic diagram of the polyimide aerogel fiber molding process.
[0062] Figure 3 The images show the morphology and structure of MoS2 nanoflowers. (a) and (b) are SEM images of MoS2 at different magnifications, respectively. (c) is the XRD pattern of MoS2. (d) is the XPS full spectrum of MoS2. (e) is the high-resolution 3d spectrum of molybdenum. (f) is the high-resolution 2p spectrum of sulfur.
[0063] Figure 4Optical photographs, SEM images, diameter distribution diagrams, and elemental distribution diagrams of polyimide aerogel fibers are shown below. Among them, (a) is an optical photograph of polyimide aerogel fibers; (b) is an SEM image of polyimide aerogel fibers; (c) is an SEM image of polyimide aerogel fibers at high magnification; (d) is a diameter distribution diagram of polyimide aerogel fibers; (e) is a distribution diagram of element C on polyimide aerogel fibers; (f) is a distribution diagram of element N on polyimide aerogel fibers; (g) is a distribution diagram of element O on polyimide aerogel fibers; (h) is a distribution diagram of element S on polyimide aerogel fibers; and (i) is a distribution diagram of element Mo on polyimide aerogel fibers.
[0064] Figure 5 The thermal conductivity of polyimide aerogel fiber fabric at different temperatures.
[0065] Figure 6 The electrical signal output capability of polyimide aerogel fiber fabric at different temperatures.
[0066] Figure 7 The voltage signal is generated by the polyimide aerogel fiber fabric under different actions. Detailed Implementation
[0067] The following is in conjunction with the appendix Figures 1 to 7 This application will be described in detail.
[0068] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0069] Chemicals and reagents Unless otherwise specified, all reagents used in the embodiments of this application are from conventional commercially available products.
[0070] The specific implementation method of this application is as follows.
[0071] Example 1 This embodiment provides a method for preparing polyimide aerogel fibers, including the following steps: S1: Imidization of fluorinated polyimide Under a nitrogen protective atmosphere, 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid were dissolved in N-methylpyrrolidone to form a transparent light orange solution. The molar ratio of 4,4'-diaminodiphenyl ether to 3,5-diaminobenzoic acid was 1:1.2. Then, hexafluorodianhydride and pyromellitic dianhydride were added, and the mixture was stirred continuously for 12 hours. The molar ratio of hexafluorodianhydride to pyromellitic dianhydride was 1:1. The reaction produced an orange transparent polyamic acid solution. Isoquinoline and copper chloride were added to a polyamic acid solution, with their mass concentrations in the reaction solution being 10 wt% and 5 wt%, respectively. The mixture was stirred continuously for 4 hours to form an organic soluble polyamic acid solution. 10 wt% of perfluoroethylene propylene copolymer and 5 wt% of molybdenum disulfide were added to an organic soluble polyamic acid solution, and the solution was treated at 100℃, 200℃ and 250℃ for 1 h each, and then heated to imidize, to obtain an imidized fluorinated polyimide solution. S2: Functionalization of imidized fluorinated polyimide A photosensitive crosslinking agent was prepared by dissolving hydroxyethyl methacrylate, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine (total amount 10 wt%) in N-methylpyrrolidone, with the ratio of the three components being 1:2:1. The imidized fluorinated polyimide solution obtained in step S1 and Irgacure 2100 photoinitiator were added to the photosensitive crosslinking agent. The mass ratio of the imidized fluorinated polyimide solution to Irgacure 2100 photoinitiator was 33:1. The mixture was stirred continuously at 25 °C for 24 h to carry out the esterification reaction and obtain a crosslinked polyimide solution, wherein the grafting rate of hydroxyethyl methacrylate was 50%. S3: Preparation of polyimide aerogel fibers The prepared cross-linked polyimide solution was subjected to conjugate electrospinning using a conjugate electrospinning device. The electrospinning process was as follows: voltage 25kV, receiving distance 18cm, liquid supply rate 0.8mL / h, ambient temperature 25℃, humidity 40%, and simultaneous ultraviolet irradiation of the spun fibers to induce sol-gel transition. The ultraviolet light intensity was 800W / m. 2 The sol-gel transition time was 10 min, and spun filaments were obtained. The spun filaments were sequentially passed through a series of condensation baths: a first bath of 40wt% HCOOH or CH3COOH aqueous solution at 45℃ for 1 hour, a second bath of deionized water at 60-90℃ for 4 hours, and a third bath of ethanol at 30℃ for 0.5 hours for solvent exchange, to obtain polyimide aerogel fibers with a core-sheath structure.
[0072] The reaction principle of the preparation method of polyimide aerogel fiber in this application is as follows: Figure 1 As shown, polyamic acid cyclization and dehydration of the fiber surface under high temperature conditions eventually form polyimide fibers.
[0073] like Figure 2 As shown, in step S3 of this application, during the preparation of polyimide aerogel fibers, the polyimide aerogel fibers are formed by cross-linking of polyimide grafted with hydroxyethyl methacrylate under ultraviolet light irradiation, and then forming polyimide aerogel fibers with a network structure through a series of water bath exchanges.
[0074] This application analyzed the MoS2 of the fluorinated polyimide prepared in step S1 of Example 1 using SEM, XRD, and XPS. The results are as follows: Figure 3 As shown, by Figure 3 It can be seen that the polyimide aerogel fiber has obvious diffraction peaks at 14.2°, 33.8°, 39.6°, 43.3°, 49.4° and 58.8°, which correspond to the (002), (101), (103), (006), (105) and (110) crystal planes of MoS2, respectively, indicating that the synthesized nanoflowers are MoS2, which fully demonstrates the successful preparation of MoS2 nanoflowers. Figure 3 Image (e) shows the high-resolution spectrum of Mo3d, which can be divided into five characteristic peaks. The characteristic peaks located at 226.18, 228.78, 232.08, 233.58, and 235.98 eV are attributed to S2s, Mo2s, and Mo2s, respectively. 4+ 3D 5 / 2 Mo 4+ 3D 3 / 2 Mo 6+ 3D 5 / 2 and Mo 6+ 3D 3 / 2 . Figure 3 (f) shows the high-resolution spectrum of S 2p, with its two main characteristic peaks located at 161.68 (S 2p). 3 / 2 ) and 163.08 eV (S 2p 1 / 2 XPS results also indicate that the prepared nanoflowers are typical MoS2.
[0075] This application performed SEM analysis on the polyimide aerogel fibers prepared in Example 1, and the results are as follows: Figure 4 As shown, Figure 4 In the middle (a), there is an optical photograph of polyimide aerogel fiber. It can be seen that due to the presence of MoS2, the nanofiber yarn prepared by conjugated electrospinning has a dark yellow appearance. Figure 4 (b) is a SEM image of a polyimide fiber yarn. It can be seen from the image that the diameter of the yarn is approximately 400 μm. Figure 4 Image (c) is a high-magnification SEM image, clearly showing particles distributed within the nanofibers, forming a bead-like structure. Analysis of the diameter of the nanofibers constituting the yarn sheath material reveals uniform thickness, with an average diameter of 419.7 nm and a diameter non-uniformity of 20.8%. Figure 4 As shown in (d). Figure 4 (e)-(i) show the distribution of C, N, O, S, and Mo elements on polyimide aerogel fibers, respectively. It can be observed that the distribution positions of S and Mo elements are related to... Figure 4In (c), the particles circled in yellow dotted lines are distributed in completely consistent positions, indicating that... Figure 4 The particles shown in (c) are MoS2, which also strongly proves that MoS2 has been successfully doped into polyimide aerogel fibers.
[0076] This application tested the porosity, density, and mechanical strength of the polyimide aerogel fibers prepared in Example 1. The porosity of the polyimide aerogel fibers prepared in Example 1 was 98%, and the density was 0.008 g / cm³. 3 Its mechanical strength is 24.8 MPa.
[0077] Application Example 1 The polyimide aerogel fibers obtained in Example 1 were woven into a fabric layer using a braiding machine. All the polyimide aerogel fibers in the fabric layer were connected by wires to obtain a fabric that constitutes a single electrode.
[0078] The thermal conductivity of the fabric comprising polyimide aerogel fibers prepared in accordance with Example 1 of this application was tested at -170-300℃, and the results are as follows: Figure 5 As shown, by Figure 5 It is known that the thermal conductivity of fabrics, including those made of polyimide aerogel fibers, gradually increases with increasing temperature, but remains lower than that of traditional fabrics. Polyimide aerogel fiber fabrics exhibit good thermal insulation properties within the temperature range of -170 to 300°C.
[0079] The open-circuit voltage (Voc) and short-circuit current (Isc) of the fabric comprising polyimide aerogel fibers prepared in accordance with Example 1 of this application were tested at 50°C, 100°C, 150°C, 200°C, and 250°C. The results are as follows: Figure 6 As shown, by Figure 6 It can be seen that at 50℃, the Voc of the fabric including polyimide aerogel fiber is 17.2V and the Isc is 41.6nA; while at 250℃, the fabric still has an electrical output of 6.8V and 29.1nA, indicating that the fabric including polyimide aerogel fiber still has good electrical output performance at 250℃.
[0080] Application Example 2 Based on the fabric prepared in Application Example 1, this application prepares an intelligent fire suit, including the fabric prepared in Application Example 1 and a signal processing and early warning module. The signal processing and early warning module includes a microprocessor, a wireless communication unit, and an alarm unit, which is used to collect electrical signals generated by a single electrode of the fabric, identify the firefighter's movement status and abnormal ambient temperature, and issue an early warning.
[0081] In an indoor environment, volunteers wearing the smart fire suit prepared in Application Example 2 tested the output signal under five different movement postures (slow walking, normal walking, fast walking, running, and jumping). The results are as follows: Figure 7 As shown, by Figure 7 It can be seen that a unidirectional waveform is generated during slow walking, with a peak voltage of approximately 1.2V and a relatively low frequency of about 0.7Hz. Fast walking and running generate higher electrical signals, with peak voltages of 12.5V and 20.3V respectively, and frequencies of 1.9Hz and 1.5Hz respectively. The electrical output performance improves with increasing amplitude of movement, indicating that the polyimide aerogel fiber can detect different motion states, thus ensuring the functionality of the smart fire suit in extreme environments and during varying movements.
[0082] Based on Example 1, this application allows for the preparation of a crosslinked polyimide solution with a grafting efficiency of 25-100% for hydroxyethyl methacrylate by adjusting the mass ratio of hydroxyethyl methacrylate, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine (within the range of 1:1:1 to 1:2:2), the mass ratio of the imidized fluorinated polyimide solution to the Irgacure 2100 photoinitiator (within the range of 20:1 to 100:1), and the temperature (20-30°C) and time (20-28h) of the esterification reaction in step S2. Lower catalyst ratios, lower temperatures, and shorter times correspond to lower grafting efficiencies, and vice versa.
[0083] The present application has been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of the present application. The descriptions of the embodiments above are only for the purpose of helping to understand the present disclosure and its core ideas. It should be noted that those skilled in the art can make several improvements and modifications to the present application without departing from the principles of the present application, and these improvements and modifications also fall within the protection scope of the claims of the present application.
Claims
1. A method for preparing polyimide aerogel fibers, characterized in that, Includes the following steps: S1: Imidization of fluorinated polyimide Under an inert gas protective atmosphere, 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid are dissolved in N-methylpyrrolidone, and then hexafluorodianhydride and pyromellitic dianhydride are added to react and generate a polyamic acid solution. Isoquinoline and copper chloride are added to a polyamic acid solution to form an organically soluble polyamic acid solution; A solution of imidized fluorinated polyimide was prepared by adding perfluoroethylene propylene copolymer and molybdenum disulfide to an organic soluble polyamic acid solution and then heating it for imidization. S2: Functionalization of imidized fluorinated polyimide A photosensitive crosslinking agent was prepared by dissolving hydroxyethyl methacrylate, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine in N-methylpyrrolidone. An imidized fluorinated polyimide solution and Irgacure 2100 photoinitiator were added to a photosensitive crosslinking agent to carry out an esterification reaction, thereby obtaining a crosslinked polyimide solution. S3: Preparation of polyimide aerogel fibers The prepared cross-linked polyimide solution was subjected to conjugated electrospinning, and the spun fibers were simultaneously subjected to ultraviolet irradiation to carry out sol-gel transformation, thereby obtaining spun filaments. Polyimide aerogel fibers with a core-sheath structure are obtained by exchanging the solvent in a condensation bath with spun filaments.
2. The method for preparing polyimide aerogel fibers as described in claim 1, characterized in that, In step S1, the molar ratio of 4,4'-diaminodiphenyl ether to 3,5-diaminobenzoic acid is 1:(1-1.3). In step S1, the molar ratio of hexafluorodianhydride to pyromellitic dianhydride is 1:(1-1.5). In step S1, isoquinoline and copper chloride are added to the polyamic acid solution, such that the mass concentrations of isoquinoline and copper chloride in the reaction solution are 5-20 wt% and 2.5-10 wt%, respectively. In step S1, the amount of perfluoroethylene propylene copolymer added is 5-20 wt%, and the amount of molybdenum disulfide added is 2.5-10 wt%, based on the theoretical yield of polyimide calculated from the total amount of hexafluorodianhydride and pyromellitic dianhydride monomers.
3. The method for preparing polyimide aerogel fibers as described in claim 1, characterized in that, In step S1, the heating imidization treatment adopts a staged heating process. The specific staged heating process is as follows: treatment is carried out at 100℃, 200℃ and 250℃ for 0.8-1.5h respectively.
4. The method for preparing polyimide aerogel fibers as described in claim 1, characterized in that, In step S2, the total amount of hydroxyethyl methacrylate, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine is 10wt%. Based on the theoretical yield of polyimide calculated from the total amount of hexafluorodianhydride and pyromellitic dianhydride monomers fed in step S1, the mass ratio of hydroxyethyl methacrylate, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine is 1:(1-2):(1-2). In step S2, the mass ratio of the imidized fluorinated polyimide solution to the Irgacure 2100 photoinitiator is (20-100):1; The process conditions for the esterification reaction in step S2 are: temperature 20-30℃, continuous stirring reaction for 20-28h.
5. The method for preparing polyimide aerogel fibers as described in claim 1, characterized in that, The grafting rate of hydroxyethyl methacrylate in the crosslinked polyimide solution obtained in step S2 is 25-100%.
6. The method for preparing polyimide aerogel fibers as described in claim 1, characterized in that, The process of conjugate electrospinning in step S3 is as follows: spinning voltage 20-30kV, receiving distance 17-21cm, and liquid supply rate 0.4-1.2mL / h; The ultraviolet radiation intensity of the ultraviolet irradiation in step S3 is 500-1000 W / m². The ambient temperature for preparing the spinning filaments in step S3 is 25-30℃ and the humidity is 36-50%.
7. The method for preparing polyimide aerogel fibers as described in claim 1, characterized in that, The process of the condensation bath in step S3 is as follows: The spinning filaments are sequentially passed through the first bath of 20-60 wt% HCOOH or CH3COOH aqueous solution, the second bath of deionized water, and the third bath of ethanol. The first bath consists of a 20-60 wt% HCOOH or CH3COOH aqueous solution at a temperature of 42-47℃, and the spinning filaments pass through the first bath for 0.8-1.5 hours. The temperature of the deionized water in the second bath is 60-90℃, and the spinning filaments pass through the second bath for 3-5 hours. The temperature of the ethanol in the third bath is 25-35℃, and the time for the spinning filaments to pass through the third bath is 0.5-1h.
8. A polyimide aerogel fiber, prepared by the preparation method according to any one of claims 1 to 7.
9. A fabric comprising polyimide aerogel fibers prepared by the preparation method according to any one of claims 1 to 7.
10. A method for preparing the fabric according to claim 9, characterized in that, Includes the following steps: Polyimide aerogel fibers are woven into fabric layers using a weaving machine; By connecting all the polyimide aerogel fibers in the fabric layer with wires, a fabric constituting a single electrode is obtained.